ANTIBACTERIAL PROPERTIES OF ZINC OXIDE NANOPARTICLES SYNTHESIZED BY THE SUPERNATANT OF WEISSELLA CONFUSA UPM22MT04 - A.I. AL-Tameemi; M.J. Masarudin; R.A. Rahim; V. Timms; B. Neilan; N.M. Isa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to produce zinc oxide nanoparticles (ZnO-NPs) using the supernatant of Weissella confusa UPM22MT04 and assess their effectiveness in inhibiting methicillin-resistant Staphylococcus aureus (MRSA). An isolate of Weissella confusa UPM22MT04 was isolated from a wastewater treatment plant in Johor, Malaysia, and was utilized to synthesize ZnO-NPs. The synthesized ZnO-NPs were characterized through several techniques, including UV-visible spectroscopy, Fourier-transform infrared spectroscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, and dynamic light scattering. Monodisperse spherical ZnO-NPs of 1.7 - 7.9 nm were obtained with 0.1 M zinc nitrate at 80°C. The biosynthesized ZnO-NPs exhibited vigorous inhibitory activity against MRSA. Results found that ZnO-NPs inhibited MRSA at a minimum concentration of 0.625 mg/mL and were bactericidal at a minimum concentration of 1.25 mg/mL. In MTT assays, ZnO-NPs showed no toxicity to HS-27 fibroblasts. The supernatant of Weissella confusa UPM22MT04 could be used to synthesize ZnO-NPs, which are an antibacterial agent, eco-friendly and non-toxic.